Transformasi bentuk Ikon Betawi Ondel-ondel dan Gigi Balang dengan Teknik Aplikasi Quilt - Dewanti, Asih Retno; Ariani, Ariani; Novianti, Erlina; Utami, Umi (Journal of Dedicators Community, 2025)
PkM Mono Semester Even Year. Academic 2022-2023 with the title Transformation of the Betawi Ondel-ondel and Gigi Balang Icons with Quilt Application Techniques was held on Saturday 18 March 2023 with Participating Partners of the Tarakanita IV Women Alumni Community –Jakarta who are entering retirement age. This activity utilizes patchwork waste to be reused into new products by elevating the local wisdom of the Betawi Icons, namely 'Ondel-ondel' and 'Gigi Balang' in decorative forms with the 'Quilt' art technique. This activity is an alternative to preserving Betawi Icons in other forms and media, namely: the application of decorative shapes, colors and symbolic meanings of Betawi Icons with Quilting Techniques. It is hoped that the results of this activity can fill free time for participating partners and as a useful social activity and can become a source of income later for participating partners. The purpose of this activity is also an extension of the Government's hand, especially the Regional Government of DKI Jakarta in improving the creative economy of participants which also makes it possible to form MSMEs. The output of mono Community Service (PkM) activities is in the form of HAKI Posters and Journal Publications.